Glioblastoma Multiforme in the over 70's: "To treat or not to treat with radiotherapy?". (4th July 2019) - Glynn, Aisling M.; Rangaswamy, Guhan; O'Shea, Julianne; Dunne, Mary; Grogan, Roger; MacNally, Stephen; Fitzpatrick, David; Faul, Clare
Abstract: Background: The incidence of Glioblastoma Multiforme (GBM) is increasing among the older population and is associated with poor prognosis. Management guidelines are lacking in this group. The purpose of this study was to analyze survival data and determine predictors of survival in patients aged ≥70 years treated with radiotherapy (RT) and/or Temozolomide. Materials and Methods: A retrospective analysis of all GBM patients treated at our institution between January 2011 and January 2017 was carried out. Results: One‐hundred and four patients were eligible. Median age was 73.8 years (70‐87). Thirty‐three patients received radical RT and 71 palliative RT. Overall median survival (MS) was 6 months. The MS was 10.6 months for radical patients and 4.9 months for palliative patients ( P  < 0.0005). The MS was 6.9 months in patients aged 70‐75 years and 5.2 months in those aged 76‐80 years ( P  = 0.004). The debulked group had a statistically significantly longer survival (8.0 months) than the biopsy only group (4.9 months). Biopsy only (hazard ratio [HR] 2.4), ECOG performance status 3 vs 0 (HR 6.4), and increasing age (HR 1.06) were associated with statistically significant shorter survival after adjustment for the effects of concurrent chemo, delay in starting RT, and RT dose. Conclusion: The MS for radical patients was favorable and approaching current literature for the under 70 age group. Radical treatment should be considered for good performance patients aged 70‐75 years. Increasing age was associated with shorter MS in patients aged ≥76 years. Debulking and good performance status were associated with improved survival. Abstract : Radical radiotherapy (RT) should be considered in well debulked, good performance status patients aged 70‐75. The impact of RT in patients ≥76 years remains questionable